Indocyanine green and fluorescence lymphangiography for sentinel node identification in patients with melanoma - Pameijer, Colette R.; Leung, Anna; Neves, Rogerio I.; Zhu, Junjia (The American journal of surgery, 2018)
Infrared fluorescence imaging with indocyanine green (ICG) is a novel method for sentinel node localization. Our objective was to assess ICG and fluorescence imaging for preoperative and intraoperative utility. 87 eligible patients participated in this prospective study. All patients received injection of ICG dye in addition to both methylene blue and 99mTc. Each sentinel node was assessed for the presence of each dye. ICG was visible prior to incision in 44% of subjects. 99mTc identified a mean of 1.89 SLN per patient. ICG identified a mean of 1.87 SLN while methylene blue (MB) dye identified a mean of 0.71 SLN. 99mTc and ICG identified the same number of sentinel nodes per patient (P = .73) while methylene blue was inferior in its ability to localize sentinel nodes (P < .001). Our findings indicate that ICG/fluorescence imaging has limited ability to identify the nodal basin preoperatively, but is equivalent to 99mTc for intraoperative identification of sentinel nodes and superior to MB. •ICG-based fluorescence imaging provides significantly better localization of sentinel nodes than MB.•ICG identifies the same number of sentinel nodes as 99mTc.•Based on our findings, ICG and fluorescence imaging can replace MB.